2020
DOI: 10.3390/genes11030238
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid 2-Glucoside Pretreatment Protects Cells from Ionizing Radiation, UVC, and Short Wavelength of UVB

Abstract: Ascorbic acid 2-glucoside (AA2G), glucosylated ascorbic acid (AA), has superior properties for bioavailability and stability compared to AA. Although AA2G has shown radioprotective properties similar to AA, effects for UV light, especially UVC and UVB, are not studied. AA2G was tested for cytotoxicity and protective effects against ionizing radiation, UVC, and broadband and narrowband UVB in Chinese hamster ovary (CHO) cells and compared to AA and dimethyl sulfoxide (DMSO). Pretreatment with DMSO, AA, and AA2G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Both pre-treatment and post-treatment AA-2G (2-glucopyranoside ascorbic acid) fibroblasts show radioresistance [111]. AA-2G is a stable form of ascorbic acid used to create cosmetics [112]. AA-2G pre-treated cells are more resistant to gamma radiation (6 Gy), and the effect of post-treatment was to reduce DNA damage (in this case DSBs).…”
Section: Vitamin C and Oxidative Dna Damagementioning
confidence: 99%
“…Both pre-treatment and post-treatment AA-2G (2-glucopyranoside ascorbic acid) fibroblasts show radioresistance [111]. AA-2G is a stable form of ascorbic acid used to create cosmetics [112]. AA-2G pre-treated cells are more resistant to gamma radiation (6 Gy), and the effect of post-treatment was to reduce DNA damage (in this case DSBs).…”
Section: Vitamin C and Oxidative Dna Damagementioning
confidence: 99%
“…One of these studies showed that UVB light, in the range of 10–1000 J/m 2 , caused a marked increase in the formation of ROS in both human and mouse keratinocytes [ 42 ]. Additionally, previous research showed ROS scavengers can reduce the cytotoxicity of UVB [ 43 , 44 ]. Our results agree with these prior studies of ROS generated by UVB, as we observed that both BB-UVB and NB-UVB were capable of inducing ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated NB-UVB was far less efficient at formation of CPDs in comparison to unfiltered BB-UVB per absorbed dose (J/m 2 ) even when the cap was on during BB-UVB irradiation. In a prior study, Maeda et al demonstrated the filtration effect of the petri dish cap being on during BB-UVB exposure [ 43 ]. Thus, we suggest that this observation may have been the result of shorter wavelengths within the BB-UVB spectrum not being able to penetrate the petri dish cap, essentially filtering the BB-UVB, which may explain the linear trend resembling that of NB-UVB.…”
Section: Discussionmentioning
confidence: 99%
“…Phillip’s germicidal UV-C lamps were used as a UV-C source with a fluence of 1 W/m 2 . Dosimetry was carried out using a UVP UVX dosimeter with a UV-C probe (UVP, Upland, CA, USA) [ 50 ]. Cell culture dishes were rotated at 6 rpm during UV-C exposure to ensure even exposure to all areas of the dish.…”
Section: Methodsmentioning
confidence: 99%